Quantification of dissolved O2 in bulk aqueous solutions and porous media using NMR relaxometry - Kurt Livo (Nature Portfolio, 2021)
Abstract Effects of dissolved paramagnetic oxygen (O2) in water on 1H nuclear magnetic resonance (NMR) Carr-Purcell-Meiboom-Gill (CPMG) experiments is evaluated at a 1H Larmor frequency of 2 MHz. Dissolution of O2 into water significantly reduces the 1H transverse relaxation coefficient (T2). For deoxygenated water, T2 is 3388 ms, water at ambient atmospheric conditions (7.4 mg/L O2) exhibits a T2 of 2465 ms, and dissolution of 2710 mg/L O2 further reduces T2 to 36 ms. The results were fit with an empirical model to facilitate prediction of T2 times for bulk water as a function of paramagnetic oxygen concentrations in solution. Dissolved O2 also greatly influences 1H NMR CPMG experiments of confined water in a model system composed of Berea sandstone. For this system, 90 mg/L O2 in H2O enhances T2 relaxation of bulk water such that the relaxation time is comparable to physically confined water in the sandstone pores. Given the sensitivity of NMR T2 coefficients to paramagnetic oxygen, low-field NMR-based characterization of fluid and porous media structure requires control of dissolved oxygen, as geospatial variation in the partial pressure of O2 alone is expected to perturb fluid and pore relaxation times by up to 60 and 36%, respectively.